Assessment of selected types of soil degradation in Syferkuil Farm using remote sensing techniques - Mamorobela, Karabo Edwin (My University, 2023)
Soil degradation is a serious environmental threat facing the humanity today. Soil degradation in one or more of its forms has been labelled as a ‘global pandemic’. This is because; soil degradation is a very serious world problem and affects all countries or continents. Thus there is an acute need to devise a way of reducing its vast advance. This is why, it is important to establish the magnitude and the extent of soil degradations in order to mitigate its effect. The objectives of this study were to:(i)Identify soils degraded by rill erosion with acceptable accuracy from remote sensing images.(ii) Determine soil organic carbon status with acceptable accuracy from remote sensing.(iii) Determine soil surface salt accumulation with acceptable accuracy from remote sensing images. The soil degradation forms consider edin this study are soil salinity, rill soil erosion and soil organic carbon. Nutrient depletion is another significant chemical process of soil degradation. Soil organic carbon depletion is a chemical degradation and in most instances is influenced by human and natural activities. The assessment of these soil degradation forms has been done in three separate chapters and detailed abstract is given at the start of each chapter. However, the general findings revealed that the prediction of those soil degradation forms from remotely sensed images did not yield good results. Nonetheless, promising performance has been recorded. Recommendations for feature studies are also provided.
Thesis M.Sc. (Soil Science)) -- University of Limpopo, 2023
Keywords: Soil degradations; Remote sensing; Multispectral imagery (sentinel 2); Regression analysis; Syferkuil farm; Soil degradation; Soil exhaustion; Remote sensing -- Equipment and supplies